2021
DOI: 10.5194/bg-18-3861-2021
|View full text |Cite
|
Sign up to set email alerts
|

The importance of antecedent vegetation and drought conditions as global drivers of burnt area

Abstract: Abstract. The seasonal and longer-term dynamics of fuel accumulation affect fire seasonality and the occurrence of extreme wildfires. Failure to account for their influence may help to explain why state-of-the-art fire models do not simulate the length and timing of the fire season or interannual variability in burnt area well. We investigated the impact of accounting for different timescales of fuel production and accumulation on burnt area using a suite of random forest regression models that included the im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…deseasonalized MDA8 ozone) (e.g. Menze et al, 2009;Kuhn-Régnier et al, 2021). Since we train the RFR five times given each possible set of 4-year training/validation data, we average the Gini importance scores for each meteorological predictor across all five runs for our final discussion below.…”
Section: Identifying and Quantifying Importance Of Meteorological Dri...mentioning
confidence: 99%
“…deseasonalized MDA8 ozone) (e.g. Menze et al, 2009;Kuhn-Régnier et al, 2021). Since we train the RFR five times given each possible set of 4-year training/validation data, we average the Gini importance scores for each meteorological predictor across all five runs for our final discussion below.…”
Section: Identifying and Quantifying Importance Of Meteorological Dri...mentioning
confidence: 99%
“…Wildfire activity is controlled by weather and climate parameters either in a time window of several months by controlling biomass growth and snowpack accumulation and hence fire fuel availability, or in shorter term by determining vegetation and duff layer moisture content and, hence, their flammability [7][8][9][10]. Analyzing wildfire activity at a global scale for different ecoregions, Abatzoglou et al [11] showed that climate variability can explain one-third of the interannual variability in burned area (BA), highlighting the controlling role of climate parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of summer conditions results in only a slight bias reduction for the extreme 2020 fire season which is underestimated by GAMs (figure 2). Failure to capture the extreme 2020 burned area extent is likely due to the rarity of the event which is not reflected in the training data [20,56]. Recent research suggests the extreme 2020 fire season was enabled by anomalously dry conditions [5]; however, burned area underestimation from our climate-based statistical models motivate future research to further understand the respective contributions of large-scale climate and factors such as local fire weather, fuel availability and ignitions to this extreme fire year.…”
Section: Pdsi Drought Areamentioning
confidence: 98%
“…Since the early 2000s, a suite of statistical analyses has quantified relationships between summer fire activity and various climate conditions in the western U.S. [3,5,[9][10][11][20][21][22]. Many of these relationships have been reviewed by Littell et al [23,24].…”
Section: Introductionmentioning
confidence: 99%